USING THE FAULT TREE AS A LOGICAL-PROBABILISTIC METHOD FOR ANALYSIS OF SHIP ELECTRIC MOTORS (Transport systems and technologies, 2022)
Despite the progress in research and development of designs of modern electric motors for industrial enterprises for various purposes, including marine electric motors, reliable methods for determining the causes of their failures have not yet been created, and the application of well-known methods in practice, including diagnosing the technical condition of engines, not only requires a lot of labor and highly qualified personnel, but in many cases it is actually inefficient. This is especially true of severe operational damage arising from the destruction of parts and accompanied by a violation of the synchronization of their reciprocating and rotational motion. On the other hand, the performed study shows that the causes of malfunctions and failures of electric motors can also be determined by logical and probabilistic methods, including on the basis of fault tree analysis involving the results of research on various faults. By structuring the signs of failures, a failure tree was compiled that logically describes the cause-and-effect relationships between the failure event and the initial damage that caused it separately for each of the failure modes selected for analysis associated with severe damage to the electric motors of the type under study. As a result of using the fault tree in practice, it is possible to determine the causes of failure of electric motors and electric motors with automatic control systems with sufficient reliability and minimal time.
Keywords: electric motor; malfunction; refusal; logical method; fault tree, control system.